2022
DOI: 10.3390/pharmaceutics14102226
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic/Pharmacodynamic Modelling of Daptomycin for Schedule Optimization in Patients with Renal Impairment

Abstract: The aims of this study are (i) to develop a population pharmacokinetic/pharmacodynamic model of daptomycin in patients with normal and impaired renal function, and (ii) to establish the optimal dose recommendation of daptomycin in clinical practice. Several structural PK models including linear and non-linear binding kinetics were evaluated. Monte Carlo simulations were conducted with a fixed combination of creatinine clearance (30–90 mL/min/1.73 m2) and body weight (50–100 kg). The final dataset included 46 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…In previous reports on the PPK of daptomycin, some were densely sampled, whereas others were sparsely sampled or directly modeled using blood drug concentration values from TDM. The final models are mostly one- or two-compartment models ( Di Paolo et al, 2013 ; Soraluce et al, 2018 ; García-Martínez et al, 2022 ). Our study found that the population pharmacokinetic model of daptomycin in critically ill adult Chinese Han patients can be described by a two-compartment model, in which clearance in non-CRRT patients can be divided into renal and non-renal clearance components, and the renal clearance component is affected by creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports on the PPK of daptomycin, some were densely sampled, whereas others were sparsely sampled or directly modeled using blood drug concentration values from TDM. The final models are mostly one- or two-compartment models ( Di Paolo et al, 2013 ; Soraluce et al, 2018 ; García-Martínez et al, 2022 ). Our study found that the population pharmacokinetic model of daptomycin in critically ill adult Chinese Han patients can be described by a two-compartment model, in which clearance in non-CRRT patients can be divided into renal and non-renal clearance components, and the renal clearance component is affected by creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%